Use of metallic ureteric stents for chronic ureteric obstruction and its association with value-based care - Yu Xi Terence Law; Ang Zhou; David Terrence Consigliere; Benjamin Yen Seow Goh; Ho Yee Tiong (Singapore Medical Journal)
Introduction: We aimed to compare the real-world data and our clinical experience with metallic stents (MSs) and conventional polymeric stents (PSs) in the management of both malignant and benign chronic ureteric obstruction (CUO), in terms of clinical outcomes and costs. Methods: Clinical data from our institution, including outcomes for all ureteric stents inserted for long-term management of CUO from all causes from 2014 to 2017, were retrospectively reviewed and compared between the MS and PS episodes. Results: A total of 247 stents were placed in 63 patients with CUO over the 4-year study period. Of these, 45 stents were MSs. There was no significant difference in all baseline characteristics between the MS and PS groups, except for the aetiology of obstructive cause. Mean indwelling stent duration was significantly greater for MS than for PS (228.6 ± 147.0 vs. 146.1 ± 66.0 days, P < 0.001), thereby leading to lower average number of stent changes per year in the MS group compared to the PS group (1.4 vs. 6.3 times, respectively). Despite the higher unit cost of MS compared to PS, there was no significant mean cost difference overall (cost per dwelling day SGD 7.82 ± SGD 10.44 vs. SGD 8.23 ± SGD 20.50, P = 0.888). Conclusion: Resonance MS is a better option than PS to manage CUO from malignant and benign causes because its significantly longer indwelling time mitigates the higher unit cost of the stent. It potentially reduces the number of procedures and operations in patients. Thus, it should be considered for all patients with CUO requiring long-term ureteric drainage.